2014
DOI: 10.3892/ol.2014.2037
|View full text |Cite
|
Sign up to set email alerts
|

Slug overexpression induces stemness and promotes hepatocellular carcinoma cell invasion and metastasis

Abstract: Detection of metastasis of hepatocellular carcinoma (HCC) is crucial for early diagnosis. Epithelial-mesenchymal transition (EMT) is a common event in the metastasis of tumor cells. Slug and Snail are homologous proteins, which play an important role in EMT. The present study aimed to investigate whether Slug and Snail overexpression is associated with the invasiveness of HCC in vitro and in vivo. Invasion, colony formation and wound healing assays, as well as flow cytometry analysis, were performed to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 26 publications
5
37
0
1
Order By: Relevance
“…Overexpression of Slug but not Snail has been reported in the HCC cell line, HepG2, to induce EMT and enhance CSC marker CD133 [69]. The EMT-CSC link may also be exploited to enrich for CSCs.…”
Section: Emt Phenotypic Cells As a Resource For Hepatic Cscsmentioning
confidence: 99%
“…Overexpression of Slug but not Snail has been reported in the HCC cell line, HepG2, to induce EMT and enhance CSC marker CD133 [69]. The EMT-CSC link may also be exploited to enrich for CSCs.…”
Section: Emt Phenotypic Cells As a Resource For Hepatic Cscsmentioning
confidence: 99%
“…Several EMT regulators, including of Twist (20, 21), Snail (21, 22), Slug (23, 24), Zeb1/2 (25, 26), β-catenin (27), FoxC1/2 (28) and Sox4 (29) are known to induce EMT in HCC cells, and their expression levels also correlate with patient survival. To further delineate the importance of these EMT regulators in HCC, we profiled their gene expression using the CCLE database and found that Twist, Snail, Slug, Zeb1/2 and β-catenin were upregulated in mesenchymal-type but downregulated in epithelial-type HCC cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cumulative evidence further emphasizes the links between EMT and CSC including their similar characteristics, such as tumorigenesis, enhanced survival signals, and metastatic ability. Mesenchymal markers including ZEB1, Snail1, and Slug are thought to be involved in CSC maintenance and tumorigenesis . SOX9 is stabilized through combination with the transcription factor Slug, promoting CSC properties and metastasis .…”
Section: Discussionmentioning
confidence: 99%